Comparative Clinical Studies On Anaesthesia Using Ketamine-Diazepam And Isoflurane In Birds - Desai, B. D.; Tank, P. H.; Nikam , P. N.; Vadalia , J. V. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
A total 20 birds affected with various kinds of injuries due to kite strings were studied. The birds were divided into two groups of 10 each. Anaesthesia was induced with Isoflurane and Ketamine Diazepam combination in group in 1 and 2, respectively. Isoflurane anaesthesia was administered using non rebreathing Ayere’s T -piece system, in other group; Ketamine-Diazepam anaesthesia was induced by I/M route. Physiological parameters viz. Heart rate and respiration rate were recorded after induction of anaesthesia every 5 minutes till the surgical procedure was over and the birds recovered from the anaesthesia. A marked salivation was observed during use of the combination of Ketamine-Diazepam. Ketamine-Diazepam combination was not found suitable for major surgery in birds because this combination accompanied by muscular tremor and myoclonic craps, and also there was increase in heart rate in comparison to the other group of anaesthesia. Recovery after use of the Isoflurane was smooth and easy in comparison to the use of the Ketamine Diazepam anaesthesia. Overall, the quality of anaesthesia (muscle relaxation, abolition of pain and minimum cardiopulmonary deviation) was significantly better and excellent in Isoflurane group of anaesthesia then the Ketamine-Diazepam group for surgery.